2015
DOI: 10.1016/j.ces.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Propane simulated in silica pores: Adsorption isotherms, molecular structure, and mobility

Abstract: Molecular dynamics simulations were conducted for bulk propane in contact with fully protonated slitshaped silica pores. The effective pore width was of either 0.8 or 2.7 nm. The temperature was set at 343, 368, and 373K. The TraPPE-UA and CLAYFF force fields were implemented to model propane and silica, respectively. Each individual simulation yields the density of confined fluid as a function of the bulk pressure. For a given temperature, adsorption isotherms were estimated by repeating the simulations at va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 58 publications
6
39
0
Order By: Relevance
“…6,7 We previously conducted extensive molecular dynamics (MD) simulations to study propane adsorption, structure and diffusion in slit-shaped silica pores at sub-, near-, and super-critical conditions. 8 The results were qualitatively consistent with the experimental adsorption isotherms reported by Gruszkiewicz et al, 9 and the SANS data reported by Rother et al 10 We recently conducted MD simulations for the structure and dynamics of CO2-butane mixtures confined within slit-shaped silica pores. 11 Preferential adsorption of carbon dioxide near the -OH groups on the surface was observed, where the adsorbed CO2 molecules tend to interact simultaneously with more than one -OH group.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…6,7 We previously conducted extensive molecular dynamics (MD) simulations to study propane adsorption, structure and diffusion in slit-shaped silica pores at sub-, near-, and super-critical conditions. 8 The results were qualitatively consistent with the experimental adsorption isotherms reported by Gruszkiewicz et al, 9 and the SANS data reported by Rother et al 10 We recently conducted MD simulations for the structure and dynamics of CO2-butane mixtures confined within slit-shaped silica pores. 11 Preferential adsorption of carbon dioxide near the -OH groups on the surface was observed, where the adsorbed CO2 molecules tend to interact simultaneously with more than one -OH group.…”
Section: Introductionsupporting
confidence: 78%
“…To obtain the planar self-diffusion coefficient Ds we calculated the mean square displacement (MSD) following established procedures. 8 To investigate the effect of CO2 loading on the mobility of confined fluids, 7 different systems were simulated whose details can be found in Table 1. As the molecular density increases, the pressure in the pore is also expected to increase.…”
Section: Simulation Models and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In mesoporous materials, propane diffusion shows a stronger dependence on loading and at higher loadings is found to have diffusion coefficients in silica aerogel (76 Â 10 À10 m 2 /s [25]) comparable to the present study. In a recent MD simulation study on propane diffusion in silica slit nanopores (2.8 nm) a much higher value of 2690 Â 10 À10 m 2 /s has been obtained for in plane diffusion [53]. The shape and size of the nanopores in this study are however quite different from our study and thus a direct comparison is difficult.…”
Section: Discussionmentioning
confidence: 59%
“…However, he treated the composite as a crystal, which may not work for pure silica aerogel. Le [17] constructed a silica cylindrical channel and simulated propane adsorption through the MD method. Only qualitative agreement with experimental results was obtained.…”
Section: Introductionmentioning
confidence: 99%